EFEKTIVITAS ADSORPSI KULIT MANGGA, KULIT PEPAYA DAN BATANG PISANG SEBAGAI PENYERAP TIMBAL (Pb) PADA AIR LINDI TPA TAMANGAPA - Saiyidah, Hijrah Mustajabah; Ihsan, Ihsan; Sahara, Sahara (Universitas Islam Negeri Alauddin Makassar, 2016)
One threat today is the destruction of the environment waste pollution. Waste of mango peel, papaya peel and banana stem bark can be used to absorb heavy metals in a body of water such as waste containing cellulose and pectin. Leachate is the result of a pile of garbage that have decomposed physical, chemical and biological decay results contain harmful substances such as heavy metals. In this study attempted an adsorption method using waste mango peel, papaya peel and banana stem as an adsorbent to absorb heavy metals in leachate is adsorbat.Â With adsorption process mango peel, papaya peel and banana stem as adsorbent divided into several mass size is 1, 1.5 and 2 grams with a variety of contact time of 40, 60 and 80 minutes as the independent variables in the study and the stirring speed as a fixed variable. Leachate used contain heavy metals Pb of 1.58 mg/l. After analysis using the SSA found that the highest effectiveness in the mango peel adsorb Pb, namely the addition of mango peel masses as much as 1 gram to 40 minutes of contact time with the absorption efficiency of 93.67%; the highest effectiveness in papaya peel adsorption of Pb, namely the addition of papaya mass of 1.5 grams with a contact time of 40 minutes with the absorption efficiency of 65.82%; the highest effectiveness in the banana stem adsorption ofÂ Pb, namely the addition of banana stem mass 1 gram with a contact time of 40 minutes with the absorption efficiency of 56.33%.